2016
DOI: 10.1186/s13570-016-0057-x
|View full text |Cite
|
Sign up to set email alerts
|

What value for pastoral livelihoods? An economic valuation of development alternatives for ephemeral wetlands in eastern Mauritania

Abstract: Pastoralism in Africa faces new challenges in an era of climate change, despite some improvements in policy and legislative frameworks as well as sporadic investment in pastoral development. There are concerns that pastoralism will not be sustainable in a climate-affected world, and this is seeing the return of policies to settle pastoralists and introduce modern cropping. Pastoralism is not yet understood as a specialisation to take advantage of instability and variability, and as a result, the trend has cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…These are of particular value to rural communities who suffer through seasons of drought, allowing them to sell these products to generate income when traditional crops are failing. In eastern Mauritania, for example, many forestry products still grow in harsh conditions, including fruits (Ziziphus mauritiana), pods of Acacia nilotica and gum Arabic (Acacia senegal) (Shine and Dunford, 2016).…”
Section: Economic Advantages Of Silvopastoralismmentioning
confidence: 99%
“…These are of particular value to rural communities who suffer through seasons of drought, allowing them to sell these products to generate income when traditional crops are failing. In eastern Mauritania, for example, many forestry products still grow in harsh conditions, including fruits (Ziziphus mauritiana), pods of Acacia nilotica and gum Arabic (Acacia senegal) (Shine and Dunford, 2016).…”
Section: Economic Advantages Of Silvopastoralismmentioning
confidence: 99%
“…Examples include irrigation schemes constructed in the East African pastoral rangelands [104][105][106]. Also in northern Nigeria [107][108][109][110], the Inner Niger delta in Mali [111][112][113][114] and parts of Mauritania [115,116]. A recent study in the arid lands of Kenya [48] demonstrated that irrigated agriculture could generate a value of US$0-4 per unit of water applied, whereas extensive production could generate US$13-22 and other domestic uses up to US$90.…”
Section: Energy Plants and Habitat Productionmentioning
confidence: 99%
“…According to IPCC (2007) report, an increasing surface temperature by about 0.2-0.3°C over the last 25 years result in reduction of rainfall and a lot of plant species from the earth. Hence, mean annual rainfall variability and increasing temperatures will have impacts on the quality and quantity of pastures (Thornton et al 2009) also reduce the grazing capacities of most rangelands (Shine and Dunford 2016), which is a critical constraints on livestock performance in the arid and semiarid ecosystems.…”
Section: Predicted Future Climate Scenariosmentioning
confidence: 99%
“…However, under the ever increasing environmental changes, the impact of rainfall variability on the productivity and vegetation dynamics of rangelands and availability of water both for human and livestock are the great challenges that the pastoral communities are facing at present in semi-arid areas of Ethiopia (Kassahun et al 2008). As a result, the carrying capacities of most rangelands in arid and semi-arid ecosystems do not sustain livestock production (IPCC 2014; Shine and Dunford 2016).…”
Section: Introductionmentioning
confidence: 99%